1993
DOI: 10.1128/jvi.67.12.7556-7560.1993
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E4orf4 protein binds to protein phosphatase 2A, and the complex down regulates E1A-enhanced junB transcription

Abstract: Adenovirus E4orf4 protein was previously shown to counteract transactivation of junB by cyclic AMP (cAMP) and EIA protein. It was also shown to cause hypophosphorylation of ElA and c-Fos proteins. Here we show that the E4orf4 protein associates with protein phosphatase 2A. All three subunits of the phosphatase are present in the complex, and the B subunit interacts directly with the viral protein. The complex possesses a phosphatase activity typical of protein phosphatase 2A, and the phosphatase mediates the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
83
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 36 publications
4
83
0
Order By: Relevance
“…Signaling pathways involving NF-κB and AP-1 contribute to transcriptional control of a variety of chemokine genes (Kaufmann et al, 2001;Roebuck et al, 1999;Shin et al, 1994;Wickremasinghe et al, 2004). Activation of NF-κB (Schmitz et al, 1996) and AP-1 (Kleinberger and Shenk, 1993;Muller et al, 1989) by E1A may thereby enhance transcription of chemokine genes in infected cells. IFN-α and IFN-γ enhance chemokine responses to influenza virus infection (Veckman et al, 2006) and rhinovirus infection (Konno et al, 2002), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling pathways involving NF-κB and AP-1 contribute to transcriptional control of a variety of chemokine genes (Kaufmann et al, 2001;Roebuck et al, 1999;Shin et al, 1994;Wickremasinghe et al, 2004). Activation of NF-κB (Schmitz et al, 1996) and AP-1 (Kleinberger and Shenk, 1993;Muller et al, 1989) by E1A may thereby enhance transcription of chemokine genes in infected cells. IFN-α and IFN-γ enhance chemokine responses to influenza virus infection (Veckman et al, 2006) and rhinovirus infection (Konno et al, 2002), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…E1A proteins exert their control on gene expression by interacting with cellular proteins through three conserved domains, conserved region (CR)1, CR2 and CR3. These interactions may influence cellular inflammatory responses via the activation of transcription factors such as NF-κB (Schmitz et al, 1996) and activating protein (AP)-1 (Kleinberger and Shenk, 1993;Muller et al, 1989). Clinical and experimental animal data have provided the basis for postulating that the human adenovirus E1A protein is responsible for immunomodulatory effects contributing to chronic lung diseases (reviewed in Hogg, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SV40 small t antigen is able to replace only the B subunit (PR55), but not the B' subunit (PR61) from trimeric PP2A (Sontag et al, 1994). It was also shown that adenovirus E4orf4 binds to the trimeric PP2A holoenzyme that contains PR55 (Kleinberger and Shenk, 1993). Taken together, these examples illustrate that the activity of PP2Ac is tightly controlled in vivo by regulatory proteins.…”
mentioning
confidence: 89%
“…Cells infected with Ad5.dl1014 demonstrate minimal adenoviral DNA replication [59]. The ability of E4orf4 to downregulate the activity of E1A proteins, either directly or via cellular intermediaries, causes the DNA replication defect when cells are infected in the absence of E4orf6 or E4orf3 by reducing the expression of viral genes dependent on the phosphorylation of the R289 residue of the E1A protein [60][61][62]. Decreased expression of these downstream viral genes would be expected to reduce systemic toxicity associated with dissemination of these vectors.…”
Section: Discussionmentioning
confidence: 99%